Lean UX : creating great products with agile teams - Gothelf, Jeff; Seiden, Josh (O'Reilly Media, 2021)
"Lean UX is synonymous with modern product design and development. By combining human-centric design, agile ways of working, and a strong business sense, designers, product managers, developers, and scrum masters around the world are making Lean UX the leading approach for digital product teams today. In the third edition of this award-winning book, authors Jeff Gothelf and Josh Seiden help you focus on the product experience rather than deliverables. You'll learn tactics for integrating user experience design, product discovery, agile methods, and product management. And you'll discover how to drive your design in short, iterative cycles to assess what works best for businesses and users. Lean UX guides you through this change--for the better. Facilitate the Lean UX process with your team with the Lean UX Canvas Ensure every project starts with clear customer-centric success criteria Understand the role of designer on an agile team Write and contribute design and experiment stories to the backlog Ensure that design work takes place in every sprint Build product discovery into your team's ""velocity""".